HUBUNGAN ANTARA MEROKOK DAN AKTIVITAS FISIK DENGAN KEJADIAN HIPERTENSI PADA PRIA DI WILAYAH KERJA PUSKESMAS SIANTAN HULU KECAMATAN PONTIANAK UTARA - ., Hengli (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: hypertension is one of community health problem inIndonesia. Hypertension got the third ranking of the most disease inPontianak city in 2011, and most happened in Siantan Hulu subdistrict.Objective: The aims of this research is to analyze the relations betweensmoking and physical activity with the occurrence of hypertension to malein Siantan Hulu subdistrict. Methods: This research was designed as across-sectional analytic observational survey. This research wasconducted in Siantan Hulu subdistrict, north Pontianak from May to Juny2012. The amount of sample were 96 respondens from the wholepopulation in Siantan Hulu subdistrict that were collected with theinstrument; the questionnaire based on inclusion and exclusion criteria.Sphygmomanometer and stetoscop for measure the blood pressure. TheSampling technique used a Probability Random Sampling with the clustersampling approach. Data analysis was conducted with comparativeanalytic technique with chi square test. Result: The result of this researchshowed there was a significant relation between smoking (p = 0,021,) withthe occurrence of hypertension and there was a significant relationbetween physical activity (p = 0,000) with the occurrence of hypertensionin Siantan Hulu subdistrict, north Pontianak. Suggestion: Suggestion inthis research is need a health promotion program for increasing thecomunities knowledge about hypertension.Keywords: smoking, physical activity, the occurrence of hypertension